Developing countries and the Millennium Round of the World Trade Organisation : a compelling case for full participation (The Council LondonGB, 1999)
Deals with principles of policy, first examining the unilateral and multilateral tracks of trade liberalisation, and the complementarities between them. Covers the political strategies which developing countries could adopt to their maximum advantage in the Millennium Round. Looks at the negotiating areas of vital importance to developing countries and the positions they should take in pursuit of their national interests.
Keywords: TRADE LIBERALIZATION